JOURNALING THERAPY DALAM MENGATASI STRES GURU BIMBINGAN DAN KONSELING SMK DI KABUPATEN BOGOR - Neng Triyaningsih Suryaman; Rindang Wahjuningtijas; Wenny Wulandari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The Guidance and Counseling Teacher profession not only plays a role in helping students' problems and achieving their developmental tasks through guidance and counseling services, but also has other workloads as an educator in schools. Vocational high school counseling guidance teachers, especially in the Bogor Regency Area, are still found to experience collisions in dealing with student behavior that leads to stress. The purpose of this study is to help vocational high school counseling guidance teachers in Bogor Regency to express thoughts and feelings in Journaling Therapy activities to overcome feelings and complaints about stress, both those that arise due to work pressure in carrying out the profession as a teacher, as well as personal problems. With this, researchers conducted a study to prove how Journaling Therapy in overcoming stress in vocational high school counseling guidance teachers in Bogor Regency. This research was conducted using a descriptive qualitative approach. The results of this study found that vocational high school counseling guidance teachers in Bogor Regency experienced a state of stress and difficulty expressing their feelings.